The Role of Perceived Ease of Use and Perceived Enjoyment in Affecting User Satisfaction on Grabfood Users in Bandung City - Rusnendar, Elan; Meilanty, Tanti; Iswardani, Dwita Leoni (iora, 2023)
The purpose of this study is to find out how much influence the Perceived ease of use and Perceived enjoyment have on User satisfaction on Grabfood users in Bandung City. The research method used in this research is descriptive and verification with a quantitative approach. The population in this study are users of the Grabfood application in Bandung City. Collecting data in this study using a questionnaire distributed to 100 respondents with probability sampling technique with purposive sampling. The results showed that partially Perceived ease of use had a significant effect on User satisfaction on Grabfood users with a tvalue of 7.328>1.984 or a significance value of 0.000 <0.05 and an coefficient value of 90.9%, The results showed that Perceived Enjoyment had a significant effect on User satisfaction on Grabfood users with a tvalue of 5.404>1.984 or a significance value of 0.000 <0.05 and an coefficient value of 89.1 % While the results of the study simultaneously show that Perceived ease of use and Perceived enjoyment have a significant influence on User satisfaction on Grabfood users with a calculated Fvalue of 643.123>3.09 and a significance value of 0.000 <0,05 and the value of coefficient is 92.8%